Essential thrombocythemia, a rare cause of cerebrovascular involvement. - Muñoz-Ríos, Mariana (2022)
Essential thrombocythemia is part of a group of chronic myeloproliferative neoplasms characterized by presenting a negative Philadelphia chromosome, among which are also polycythemia vera and primary myelofibrosis. The aim of this literature review was to clarify the relationship between essential thrombocythemia and cerebrovascular involvement. A search was performed in the databases PubMed, Scielo, Google Scholar, using the descriptors: Myeloprofeliferative neoplasms, essential thrombocythemia, cerebrovascular accident, intracranial thrombosis, janus kinase 2, calreticulin; a total of 70 articles were found from which 50 articles published in the last 5 years were selected. Ischemic stroke, hemorrhagic stroke, dural sinus thrombosis and cerebral venous thrombosis may be complications of essential thrombocythemia, which, although a rare etiology, should be taken into account, since complications are the main cause of mortality in patients with this disease.